Crisis Management in Small and Medium Entrepreneurs in Azerbaijan - Deliduman, Kivilcim (ADA University, 2022)
In the business world, which has become globalized and increasingly interdependent and has a more complex structure in all areas of life, but especially in economic, social, legal and political fields, adversities have been experienced one after another and will continue to be experienced. As a result of this, the negativities in any region or country have reflections on other countries in the form of crisis. Although these effects and their consequences vary from country to country, from sector to sector, they affect the entire working life and therefore people. Not every negativity experienced by organizations is considered a crisis, but developments that threaten the existence of the organization and disrupt its continuity are considered a crisis. However, whether the source of the crisis is local or global, whether it is caused by natural disasters or epidemics, competition or management, all crises have reflections on organizations. Regardless of the reason, the reflections and effects of the crises that are not managed well on the organizations show themselves as resource shortages and economic losses due to the decrease in income. Organizations that do not learn from their experiences despite experiencing such frequent and many crises often do not know what to do, and they endanger both their own future and the future of other organizations with which they are in relationship with the wrong decisions they take. While some of the crises can be foreseen, some are difficult to predict, but still, most of the organizations are unprepared even for the crises they are sure to come. While the economic indicators of 2019 indicate that the public and private debt stock is high and that this may trigger a crisis, it is possible to see it in the deepening crisis with the rapidly spreading COVID-19 epidemic. This unpreparedness also affects the management of the crisis process. It is for this reason that nearly three-quarters (74%) of organizations seek outside help to overcome the crisis (PwC, 2019). The study will be conducted on 45 Small and Medium Enterprises operating in Azerbaijan and a research strategy will be used to investigate the findings. The relationship between the variables will determine the relevance of the measures taken during the crisis to the outcome of the pre-arranged plans. Finally, company executives will be advised on the steps they need to take to improve the measures to be taken before and during the crisis.
Keywords: Business; Crisis Management.; Small Entrepreneurship.; Medium Entrepreneurship.